Temperature responses in a subarctic springtail from two geothermally warmed habitats - Kutcherov, Dmitry; Slotsbo, Stine; Sigurdsson, Bjarni D.; Leblans, Niki; Berg, Matty P.; Ellers, Jacintha; Marien, Janine; Holmstrup, Martin (Pedobiologia, 2020)
Abstract: Common-garden experiments with populations sampled along natural thermal gradients help to reveal local adaptation, disentangle environmental and genetic effects, and ultimately predict, by analogy, future biotic responses to climate change. In this regard, geothermal habitats are useful model systems as they exhibit dramatic changes in soil temperature. The springtail Protaphorura pseudovanderdrifti has apparently coped with such local geothermal warming in Iceland, as this species occurs along a more than half-century-old geothermal gradient in a grassland and persists along a newly emerged temperature gradient in a previously non-geothermal planted spruce forest. We measured thermal reaction norms for development and walking speed and acute cold shock tolerance of P. pseudovanderdrifti originating from the grassland and forest geothermal gradients. Temperature-dependent juvenile development showed little variation among subpopulations from the recently warmed forest, probably due to insufficient evolutionary time, but springtails from the warmed grassland plots had significantly steeper reaction norms than their counterparts from the corresponding unwarmed plot. In contrast, cold tolerance and locomotory activity showed no conclusive clinal pattern despite significant within-habitat variation. There appeared to be significant differences between habitats, as springtails from the forest had more temperature-sensitive developmental rate and locomotory activity, walked faster, and exhibited more variable cold tolerance than grassland springtails did. The planting of a forest, therefore, seems to have exerted a stronger effect on the thermal phenotype of P. pseudovanderdrifti than the emergence of a geothermal gradient. Thus, habitat properties may be no less important in shaping thermal reaction norms than the mean temperature. These local-scale findings suggest that, in addition to warming per se, global transformation of communities may drive the evolution of thermal phenotypes to an extent ...